Emerging roles of deubiquitinating enzymes in human cancer - Yang Jin-ming (Acta Pharmacologica Sinica; Vol 28, No 9 (September 2007): Acta Pharmacologica Sinica（Special Issue on molecular targets, biomarkers and animal models for anti-cancer pharmacological research: potentials and challenges from chemoprevention to chemotherapeutic treatment）, 2016)
Protein modifications by the covalent linkage of ubiquitin have significant involvement in many cellular processes, including stress response, oncogenesis, viral infection, transcription, protein turnover, organelle biogenesis, DNA repair, cellular differentiation, and cell cycle control. Protein ubiquitination and subsequent degradation by the proteasome require the participation of both ubiquitinating enzymes and deubiquitinating enzymes. Although deubiquitinating enzymes constitute a large family in the ubiquitin system, the study of this class of proteins is still in its infant stage. Recent studies have revealed a variety of molecular and biological functions of deubiquitinating enzymes and their association with human diseases. In this review we will discuss the possible roles that deubiquitinating enzymes may play in cancers.